L'égalité des chances à l'épreuve de la massification à l'université Omar Bongo de Libreville. Du discours politique à la réalité de l'offre universitaire - Dany Daniel Bekale
This contribution is intended to test the rhetoric of equal opportunity at Omar Bongo University in Libreville with regard to the conditions of study and life of students. From this perspective, the question that serves as a guideline for this knowledge project is how to talk about equal opportunities in a context marked by various forms of precariousness. In order to answer this question, the methodological approach is based on a content analysis of political discourse cross-referenced with an examination of official statistics.